2021
DOI: 10.1186/s43044-021-00157-6
|View full text |Cite
|
Sign up to set email alerts
|

Coronary tortuosity relation with carotid intima-media thickness, coronary artery disease risk factors, and diastolic dysfunction: is it a marker of early atherosclerosis?

Abstract: Background Coronary tortuosity (C-Tor) is a common finding in coronary angiography (CAG). There are conflicting data about its link to atherosclerosis: one study found a negative relationship with coronary artery disease (CAD), although it had been linked to age and hypertension (HTN), which are CAD risk factors. Carotid intima-media thickness (C-IMT) is a measure of early atherosclerosis and a surrogate for CAD, diastolic dysfunction is also associated with CAD risk factors. In this retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We read with interest the thoughtful paper by Ahmed Alamragy et al [1] that highlighted the association of coronary artery tortuosity (CAT) with increased carotid intima-media thickness (CIMT), hypertension, hyperlipidemia, left ventricular diastolic dysfunction (DD), and coronary artery atherosclerosis, so this study contributes well to the existing literature especially if we consider how common is this socalled benign coronary phenotype and how limited data are there regarding its significance. Nevertheless, there are certain issues that we would like to raise regarding this study.…”
Section: Zainab Atiyah Dakhilmentioning
confidence: 85%
“…We read with interest the thoughtful paper by Ahmed Alamragy et al [1] that highlighted the association of coronary artery tortuosity (CAT) with increased carotid intima-media thickness (CIMT), hypertension, hyperlipidemia, left ventricular diastolic dysfunction (DD), and coronary artery atherosclerosis, so this study contributes well to the existing literature especially if we consider how common is this socalled benign coronary phenotype and how limited data are there regarding its significance. Nevertheless, there are certain issues that we would like to raise regarding this study.…”
Section: Zainab Atiyah Dakhilmentioning
confidence: 85%
“…Interestingly, a review of a cohort of SCAD patients with known FMD showed 45% of the patients to be postmenopausal and 27% to have a history of migraines. 16 Histological analysis of FMD patients with SCAD has showed that there is the typical FMD vascular changes such as circumferential intimal 36 thickening and fibrosis and no evidence of vasculitis, atherosclerotic changes, or cystic medial necrosis at sites of dissections. 28,29 In terms of the clinical course of FMD patients presenting with SCAD, there was no association between the prevalence of FMD and SCAD recurrence and long-term adverse events after initial presentation.…”
Section: Fibromuscular Dysplasiamentioning
confidence: 99%
“…3). 26,36 While coronary artery tortuosity has been seen more commonly in patients who are female, of advanced age, or have chronic HTN, the exact mechanism of its development is unclear. 26,37 Coronary artery tortuosity has also been seen in other connective tissue diseases including FMD.…”
Section: Other Arteriopathiesmentioning
confidence: 99%
See 1 more Smart Citation